Poverty, gender, and water issues in irrigated agriculture and irrigation institutions: mainstreaming gender in water resources management - Upadhyay, Bhawana (2003)
Research highlight based on a paper titled Poverty, gender and water issues in irrigation agriculture and irrigation institutions: A review of literature?